Implementasi Identitas Kependudukan Digital Dalam Upaya Pengamanan Data pribadi - Ikhsan Bagus Permadi; Ali Rokhman (JOPPAS: Journal of Public Policy and Administration Silampari, 2023)
In every public service process, the public is required to fill in personal data in the registration form, both manually and online. Online services provide great benefits because they speed up the service process and can be done anywhere. But on the other hand, providing personal data through online networks is very vulnerable to personal data security. By providing personal data, it is very likely that population data will be misused by irresponsible parties, causing harm to the owner of the personal data. The Department of Population and Civil Registration of Banyumas Regency as a public service agency authorized to issue population documents containing all personal data makes efforts to secure Electronic Identity Card data by implementing an Android-based Digital Population Identity. The purpose of this study was to find out how far the implementation of Digital Population Identity at the Banyumas Regency Population and Registration Office is in an effort to protect people's personal data, the obstacles faced and the benefits to be achieved. This research uses qualitative methods with various relevant sources. The results of the research need for continuous outreach regarding activation procedures and the benefits of applying Digital Citizenship Identity as a substitute for Electronic Identity Cards